9(2w−y)=21w−9y
First you multiply the numbers in the parenthesis by 9
![18w-9y=21w-9y](https://tex.z-dn.net/?f=18w-9y%3D21w-9y)
subtract. 21w-18w=3w
![-9y=3w-9y](https://tex.z-dn.net/?f=-9y%3D3w-9y)
add. -9y+9y=0
![0=3w](https://tex.z-dn.net/?f=0%3D3w)
divide.
![0=w](https://tex.z-dn.net/?f=0%3Dw)
Final answer is 0.
Answer:
5/6 or 4/6
Step-by-step explanation:
6-2=
4/6 -with out two
5/6 -including two
Answer: (0.8468, 0.8764)
Step-by-step explanation:
Formula to find the confidence interval for population proportion is given by :-
![\hat{p}\pm z^*\sqrt{\dfrac{\hat{p}(1-\hat{p})}{n}}](https://tex.z-dn.net/?f=%5Chat%7Bp%7D%5Cpm%20z%5E%2A%5Csqrt%7B%5Cdfrac%7B%5Chat%7Bp%7D%281-%5Chat%7Bp%7D%29%7D%7Bn%7D%7D)
, where
= sample proportion.
z* = Critical value
n= Sample size.
Let p be the true proportion of GSU Juniors who believe that they will, immediately, be employed after graduation.
Given : Sample size = 3597
Number of students believe that they will find a job immediately after graduation= 3099
Then, ![\hat{p}=\dfrac{3099}{3597}\approx0.8616](https://tex.z-dn.net/?f=%5Chat%7Bp%7D%3D%5Cdfrac%7B3099%7D%7B3597%7D%5Capprox0.8616)
We know that , Critical value for 99% confidence interval = z*=2.576 (By z-table)
The 99 % confidence interval for the proportion of GSU Juniors who believe that they will, immediately, be employed after graduation will be
![0.8616\pm(2.576)\sqrt{\dfrac{0.8616(1-0.8616)}{3597}}](https://tex.z-dn.net/?f=0.8616%5Cpm%282.576%29%5Csqrt%7B%5Cdfrac%7B0.8616%281-0.8616%29%7D%7B3597%7D%7D)
![0.8616\pm (2.576)\sqrt{0.0000331513594662}](https://tex.z-dn.net/?f=0.8616%5Cpm%20%282.576%29%5Csqrt%7B0.0000331513594662%7D)
Hence, the 99 % confidence interval for the proportion of GSU Juniors who believe that they will, immediately, be employed after graduation. = (0.8468, 0.8764)
Answer:
it is a rectangular prism
Step-by-step explanation:
it is 3D and when something has four faces that are rectangular and two that are sqaure it makes it a rectangular prism. imagine the rectangles on the sides and sqares at the end, it looks like a rectangle =).
Answer:
B
Step-by-step explanation:
let y = f(x) and rearrange making x the subject, that is
y = x - 3 ( add 3 to both sides )
y + 3 = x
change y back into terms of x, then
(x) = x + 3 → B